2009
DOI: 10.3347/kjp.2009.47.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Infectivity Change of Cryptosporidium parvum after Gamma Irradiation

Abstract: Cryptosporidium parvum is an obligate intracellular protozoan that infects a wide range of vertebrates, including humans and animals [1]. Most infections are acquired from water or food contaminated with infectious oocysts [2,3]. Cryptosporidium has been a threat to the water industry and public health since 1980 when AIDS became a public health issue, and its low infection dose and high resistance to various disinfectants facilitate its high infection rate [4][5][6].Gamma irradiation has been used to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Immunization of rabbits against eimeriosis by different attenuated sporulated Eimeria oocysts on experimentally infected rabbits with this attenuated oocysts showed a pre-patent period 5-6 days. Our result close ratio is consistent with that of Akpo et al(2012) The current result showed that the degree of clinical symptoms was decreased in the attenuated groups than that of the control group, this result was in agreement with that of Lee et al(2009) who recorded that Cryptosporidium parvum oocysts where subjected to gamma irradiation at various doses (1,5,10,and 25 kGy) showed reduction of the infectivity and repair of the infectivity after irradiation and Ramadan et al (2018)who reported that immunization of lambs by using one hour UV irradiated Eimeria oocysts showed no signs of recumbency, fever and off food ,only lambs showed soft feces at 13 th PI and, while our result were disagreed with Ramamoorthy et al(2006) who evaluated that vaccination of female mice with two intraperitoneal inoculation of 1x10 6 of 528 Gy of gamma irradiated Neospora caninum tachyzoites and challenged intraperitoneally with 1x10 7 N. caninum tachyzoites. All vaccinated mice remained healthy and showed no obvious signs of neosporosis.…”
Section: Discussionsupporting
confidence: 93%
“…Immunization of rabbits against eimeriosis by different attenuated sporulated Eimeria oocysts on experimentally infected rabbits with this attenuated oocysts showed a pre-patent period 5-6 days. Our result close ratio is consistent with that of Akpo et al(2012) The current result showed that the degree of clinical symptoms was decreased in the attenuated groups than that of the control group, this result was in agreement with that of Lee et al(2009) who recorded that Cryptosporidium parvum oocysts where subjected to gamma irradiation at various doses (1,5,10,and 25 kGy) showed reduction of the infectivity and repair of the infectivity after irradiation and Ramadan et al (2018)who reported that immunization of lambs by using one hour UV irradiated Eimeria oocysts showed no signs of recumbency, fever and off food ,only lambs showed soft feces at 13 th PI and, while our result were disagreed with Ramamoorthy et al(2006) who evaluated that vaccination of female mice with two intraperitoneal inoculation of 1x10 6 of 528 Gy of gamma irradiated Neospora caninum tachyzoites and challenged intraperitoneally with 1x10 7 N. caninum tachyzoites. All vaccinated mice remained healthy and showed no obvious signs of neosporosis.…”
Section: Discussionsupporting
confidence: 93%
“…Since the early nineties, cobalt-60, a type of gamma radiation, has been used on food to control infectivity of several parasites as Paragonimus westermani [13] , Metagonimus yokogawai [14] , Eimeria tenella [15] , Toxoplasma gondii [16] , Angiostrongylus cantonensis [17] , Taenia solium [18] , Clonorchis sinensis [19] , Cryptosporidium parvum [20] , Ascaris lumbricoides [21] , Trypanosoma cruzi [22] and Echinococcus granulosus [23] . UV irradiation usage for the disinfection of drinking water was first applied in 1910 in Marseille.…”
Section: Introductionmentioning
confidence: 99%
“…This is the highest reported resistance to irradiation among parasites. In a recent report, the infectivity of C. parvum oocysts in HCT-8 cells was reduced under 3 log 10 by 10 kGy irradiation [ 6 ]. Since the dose of C. parvum required for infection is known to be quite low [ 7 ], even 0.1% of oocysts that maintain infectivity still pose a threat to the host.…”
Section: Introductionmentioning
confidence: 99%